2007
DOI: 10.1111/j.1365-2850.2007.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diagnosis and non‐compliance attributions on therapeutic alliance processes in adult acute psychiatric settings

Abstract: To investigate the effects of the diagnoses of borderline personality disorder (BPD) and major depressive disorder (MDD), together with reasons for client non-compliance with therapy tasks, on mental health workers' helping, empathy and anger reactions. Utilizing a 2 x 2 x 2 factorial design, mental health nurses were asked to read a series of vignettes and complete a 15-item rating scale for helping, empathy and anger reactions to each of the vignettes. Eight clinical vignettes were constructed and contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…In contrast, nurses are more likely to respond with sad and self-critical feelings towards psychotic service users and with warm and helpful feelings towards those with neurosis [16]. Other findings suggest that nurses may perceive service users with a BPD to have a greater degree of control over the negative behaviours they display, when compared to those with other disorders [12, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nurses are more likely to respond with sad and self-critical feelings towards psychotic service users and with warm and helpful feelings towards those with neurosis [16]. Other findings suggest that nurses may perceive service users with a BPD to have a greater degree of control over the negative behaviours they display, when compared to those with other disorders [12, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Nursing staff may respond more negatively to people with BPD than other disorders, e.g. schizophrenia and depression (Markham & Trower, 2003;Forsyth 2007;Westwood & Baker, 2010), and may also be less optimistic about the potential of people with BPD to recover (Markham & Trower 2003), viewing them as more difficult to care for compared to other service users (James & Cowman, 2007;Howes, Weaver, & Tyrer, 2008). Woollaston & Hixenbaugh, 2008 found that some nursing staff felt they lacked the necessary skills to work with people with BPD, but wanted to improve their practice with this service user group.…”
Section: Introductionmentioning
confidence: 99%
“…A suggested reason for this is that these clients are seen as healthier than other patients, therefore when they display challenging behaviours such as self harm or anger, nurses become less empathetic and withdraw (Fraser and Gallop 1993). Further research supports this theory by proposing that BPD patients have greater control over their behaviours than patients with other diagnoses, with the result that any negative behaviour is seen as deliberate (Markham and Trower 2003;Forsyth 2007). Markham and Trower's (2003) study was limited because participants were aware they were being asked about attitudes to different groups of patients so may have changed their answers accordingly (Westwood and Baker 2010), but these findings do resonate with the literature around this topic.…”
Section: Criterion -Borderline Personality Disordermentioning
confidence: 67%